The Beauty Myth and Male Gaze in Emeron Lovely Hand & Body Lotion Advertisements - Helnaz, Regina Nopia; Suharjo, Rias Antho Rahmi (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
This study critically examines the representation of beauty myth and male gaze in Emeron hand and body lotion advertisements. Grounded in Naomi Wolf’s theory of the beauty myth and Laura Mulvey’s concept of the male gaze, the research analyzes how these frameworks shape the portrayal of women in beauty product marketing. Using Sandelowski’s purposive sampling method, the study selects two beauty advertisements for analysis: Emeron Lovely Step Pink (2013) and Emeron Lovely Naturals (2023), both published on the official YouTube channels of Lion Wings and Emeron Lovely Official. Through visual and narrative analysis, the findings reveal that both advertisements emphasize idealized female beauty, characterized by white, smooth, radiant, soft, moisturized, and fragrant skin, framing these attributes as essential for women’s desirability. Although the products are targeted toward women, the advertisements employ camera techniques such as selective cropping and zoom-ins on body parts like legs, hands, and shoulders, subtly reinforcing the male gaze. These techniques contribute to the objectification of women and suggest that their self-worth and confidence are contingent upon male approval. Furthermore, the female figures in the advertisements appear to internalize and affirm these patriarchal ideals. By highlighting the persistence of gendered power dynamics in beauty advertising, this study contributes to broader discussions in gender and media studies, particularly regarding how commercial media continues to shape and constrain female identity.